“I am forced to speak, but it’s okay”: Black Box for Students with Lower Levels of Willingness to Communicate - Atikah, Dewi; Sukmawati, Sukmawati; Takulani, Abd Haris; Safei, Nur Hasanah (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study aims to investigate students’ perceptions of the “Black Box” technique and its influence on their Willingness to Communicate (WTC) in an EFL classroom. Prior to examining students’ perceptions, their WTC levels were identified using WTC indicators adapted from Weaver’s work (2015). Data were collected through a close-ended questionnaire, reflection questions, and semi-structured interviews. The results indicate that the students were at moderate and high levels of WTC. Five major themes were identified using Braun and Clarke’s (2017) thematic analysis: general impression and awareness of Black Box, engagement and interest, learning experience, learning impact, and challenges and benefits of implementation. Findings reveal that both moderate- and high-WTC students perceived the use of Black Box positively, although in slightly different ways. The technique appeared to foster students’ psychosocial states, such as confidence, reduced anxiety, and a sense of security during communication, which in turn encouraged them to speak more willingly in English. Overall, the Black Box can serve as an alternative pedagogical approach to enhance students’ communicative participation. However, the results are context-specific and limited to one classroom setting; therefore, broader generalizations should be made with caution.